2002
DOI: 10.1002/clc.4950250805
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of cardiac myxoma with constitutional signs: A multicenter study in Japan

Abstract: Background: A relationship between constitutional signs in patients with cardiac myxoma and interleukin‐6 has been Noted. However, there is little information about characteristics of cardiac myxomas associated with constitutional signs. Hypothesis: The objective of this study was to clarify the characteristics of myxoma patients who had constitutional signs. Methods: Questionnaires were sent to cardiology or cardiovascular surgery divisions at university hospitals throughout Japan. Constitutional signs were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 17 publications
(29 reference statements)
2
15
2
Order By: Relevance
“…The first successful surgical resection of a cardiac myxoma was performed with a cardiopulmonary bypass in 1954. 14,15 In concurrence with our series, patients with cardiac myxomas are reported to have a wide age range (17-76 years), with a mean age of approximately 45 years. There appears to be a slight female predominance, with a female-to-male ratio of 5:4.…”
Section: Discussionsupporting
confidence: 89%
“…The first successful surgical resection of a cardiac myxoma was performed with a cardiopulmonary bypass in 1954. 14,15 In concurrence with our series, patients with cardiac myxomas are reported to have a wide age range (17-76 years), with a mean age of approximately 45 years. There appears to be a slight female predominance, with a female-to-male ratio of 5:4.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies with relatively large sample sizes (n = 124-323) reported that 82-94% of cardiac tumors were benign and 6-18% were malignant [6,7,11,15], which were consistent with the present study. The proportion of myxomas among primary cardiac tumors was 78-89% in the present study and previous Japanese studies [7,15] compared with 42-50% in previous American studies [6,11].…”
Section: Comparison With Previous Studiessupporting
confidence: 94%
“…The proportion of myxomas among primary cardiac tumors was 78-89% in the present study and previous Japanese studies [7,15] compared with 42-50% in previous American studies [6,11]. This difference may be attributable to racial differences between American and Japanese patients.…”
Section: Comparison With Previous Studiescontrasting
confidence: 79%
See 1 more Smart Citation
“…These signs are more frequent for patients with large, multiple, or recurrent tumors [25], and are for the most part reversible upon resection [12,25,34,76]. The results of lab- oratory investigations may therefore sometimes mimic those for rheumatic or autoimmune disease [34].…”
Section: Clinical Features and Therapeutic Approachmentioning
confidence: 99%